Amalan Tawassul Dalam Ilmu Tarekat - Faudzinaim Badaruddin; Muhammad Khairi Mahyuddin (MUFTI OF FEDERAL TERRITORY'S OFFICE\r\nPRIME MINISTE, 2024)
Vol. 1 No. 2 (2022): Journal of Ifta and Islamic Heritage